Educating, Training, and Mentoring Minority Faculty and Other Trainees in Mental Health Services Research - Yager, Joel (2007)
OBJECTIVE: The authors describe the evolution of a novel national training program to develop minority faculty for mental health services research careers. Recruiting, training, and sustaining minority health professionals for academic research careers in mental health services research have proven challenging. METHOD: Over the past 8 years the authors developed NIMH-funded programs to educate, train, and mentor minority psychiatrists and other junior faculty and graduate and post-graduate students. Their areas of academic interest focus primarily on minority mental health issues in primary care and community settings. RESULTS: The authors began with a program that targeted local trainees from the University of New Mexico and expanded to regional and national programs offering weeklong institutes, onsite and distance mentoring by experts, and supportive peer interactions that addressed the considerable challenges affecting trainee career decisions and paths. CONCLUSIONS: Early outcomes support the value of these programs.